Coroners in London and Middlesex, c. 1820–1888: A Study of Medicalization and Professionalization - Fisher, Yvonne King (2020)
The nineteenth century was a period of reform and transition for the office of coroner. Despite its antiquity and its place at the heart of the investigation into sudden and unexplained deaths, various social, political and intellectual changes resulted in a growing debate about the purpose, role and functions of the coronership. Many commentators, as well as coroners themselves, believed the office needed reform. This thesis considers debates about the office of the coroner from c. 1820 to c. 1888, a period that covers the wide-ranging attempts to reform the coronial office by the London coroner Thomas Wakley in the 1820s to the legislative initiatives of the 1880s that shaped the office for the next century. In particular it assesses the extent to which these debates relate to two broad concepts: medicalization and professionalization. For some, the future of the coronial office lay in the increasing application of medical expertise to the inquest, even to the extent of turning the coronership into an exclusively medical role. This study assesses how far such ‘medicalizing’ tendencies impacted on the office. Likewise, it considers whether the office underwent a process of professionalization during the nineteenth century. By considering guides to coronial practice, legislation and the formation and activities of the Coroners’ Society of England and Wales, it explores whether the coronership became a profession over the course of the century. These debates are viewed through a focus on coroners from London and Middlesex, since as a group they were at the forefront of debates. Working in the challenging environment of the metropolis, and close to the centres of political, legal, scientific and medical authority, London and Middlesex coroners such as Wakley, William Baker, William Payne, Edwin Lankester and Samuel Langham were prominent advocates of coronial reform. The thesis assesses how far coronial change was being driven from London; it suggests that there were different phases in the reforming process, each of which was closely associated with London and Middlesex coroners, and which together brought about important reforms that professionalized the office and created a medico-legal (that is, informed and shaped by the disciplines of both medicine and law), if not medicalized, inquest